Hubungan Antara Paritas Dengan Tingkat Kecemasan Ibu Hamil Di Griya Arin, Yogyakarta - Anggraeni, Fatimah Dewi; Utami, Nendhi Wahyunia; Rahmawati, Dechoni (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
Approximately 10% of pregnant women experience depression and this condition is higher in developing countries, reaching 15.6% during pregnancy and 19.8% after delivery. Mothers who experience anxiety during pregnancy will affect the intrauterine environment and fetal development. The majority of Primigravida mothers do not have experience and how to handle pregnancy until the delivery process goes smoothly, causing anxiety when compared to multigravidas. The purpose of this study was to determine the relationship between parity and anxiety levels. To determine the relationship between parity and the anxiety level of pregnant women with TM II and III. The type of research used is an analytic survey with a cross sectional approach. The population in this study were all pregnant women with TM II and III at Griya Arin using a purposive random sampling technique with a total of 30 respondents. The data analysis used was the Spearman rho correlation nonparametric statistical test.The parity of most pregnant women in the multigravida pregnancy category was 60% (18 people), while the anxiety level of most pregnant women was in the moderate category, namely 73.3% (22 people). There is a parity relationship with the level of anxiety in pregnant women at Griya Arin Yogyakarta with a p-value of 0.039 and an odds ratio of 1.000 . There is a relationship between parity and the level of anxiety in pregnant women at Griya Arin Yogyakarta.